Cliques, hicks, and ugly sticks - McCrite, K. D. (Kathaleen Deiser) (Nashville, Tenn. : Tommy Nelson, 2011)
Autumn of 1986 in the Ozarks finds eleven-year-old April Grace adjusting to middle school, coping with her mother's difficult pregnancy, helping Isabel with the church play, and trying to figure out why the new boy at school will not leave her alone.
860
Keywords: Christian life -- Juvenile fiction; Family life -- Arkansas -- Juvenile fiction; Farm life -- Arkansas -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Theater -- Juvenile fiction; Arkansas -- History -- 20th century -- Juvenile fiction; Christian fiction